STUDI KEPEMIMPINAN MUHAMMAD AL-FATIH DALAM BUKU MUHAMMAD AL-FATIH SANG PENAKLUK KONSTANTINOPEL KARYA JOHN FREELY - Mulyadi , Zulkifli (J-MD Jurnal Manajemen Dakwah, 2021)
Leadership is an important component which could not be separated from human life. One of the success leaders in history of Islamic civilization was Muhammad Al-Fatih. He managed to conquer Constantinople by such brilliant strategies. The purpose of this research is to find out: 1) The leadership character of Muhammad Al-Fatih; 2) Muhammad Al-Fatih's leadership style; 3) Relevance of the value of Muhammad Al-Fatih's leadership. This research includes qualitative research with a library study approach. The data source is taken from various literature related to Muhammad Al-Fatih. The research procedure used is to search various literature, read, filter, and mark the processed parts into the report. Based on the analysis, researchers can conclude that Muhmmad Al-Fatih’s leadership which can be modelled especially for the young generation. Moreover, Indonesia will get demographic bonus that must be utilized as well for a better development. This conclusion is strengthened by some specific conclusions, those are: 1) Muhammad Al-Fatih was a Muslim leader who always had the reason behind his actions; 2) Muhammad Al-Fatih has charisma in leading his army; 3) Good character and charismatic leadership style are very relevant to apply in this day and age. Keywords: Character, Leadership, Relevance.